Experimental methods in chemical engineering: X‐ray diffraction spectroscopy—XRD. (3rd April 2020) - Khan, Hayat; Yerramilli, Aditya S.; D'Oliveira, Adrien; Alford, Terry L.; Boffito, Daria C.; Patience, Gregory S.
Abstract: X‐ray diffraction (XRD) analysis identifies the long‐range order (ie, the structure) of crystalline materials and the short‐range order of non‐crystalline materials. From this information we deduce lattice constants and phases, average grain size, degree of crystallinity, and crystal defects. Advanced XRD provides information about strain, texture, crystalline symmetry, and electron density. When radiation impinges upon a solid, coherent scattering of the radiation by periodically spaced atoms results in scattered beams that produce spot patterns from single crystalline samples and ring patterns from polycrystalline samples. The pattern, intensities of the diffraction maxima (peaks or lines), and their position (Bragg angle θ or interplanar spacing d hkl ), correlate to a specific crystal structure. In 2016 and 2017 close to 100 000 articles mention XRD—more than any other analytical technique, and it was the top analytical technique of researchers that published in Can. J. Chem. Eng. A bibliographic analysis based on the Web of Science groups articles referring to XRD into five clusters: the largest cluster includes research on nanoparticles, thin films, and optical properties; composites, electro‐chemistry, and synthesis are topics of the second largest cluster; crystal morphology and catalysis are next; photocatalysis and solar cells comprise the fourth largest cluster; and, waste water is among the topics of the cluster with the least number of occurrences. Researchers publishing in Can. J. Chem. Eng. focus most of the XRD analyses to characterize polymers, nanocomposite materials, and catalysts.